Calculation Method of IGBT Junction Temperature Based on Heat Conduction Model - Xin CHEN; Yiming WANG; Peng WANG (机车电传动)
Aiming at the problem that the junction temperature of IGBT chip is difficult to measure directly, a calculation method of IGBT junction temperature based on heat conduction model was proposed. The heat conduction model of the converter was established based on the classic Cauer RC network structure; the parameter identification of the heat conduction model of the converter was completed by combining the concept of transfer function and the structure of heat conduction model; the real-time power loss of the IGBT was calculated by consulting the IGBT product manual and the actual working conditions; finally, the simulation calculation was carried out by MATLAB/Simulink, and the real-time junction temperature of IGBT chip on the converter was obtained. This method realizes the fast calculation of IGBT chip junction temperature, provides important data support for IGBT reliability and life evaluation, and provides a new scientific basis for the design and development of power modules and converters.